2013
DOI: 10.1213/ane.0b013e318270a6d9
|View full text |Cite
|
Sign up to set email alerts
|

Beat-to-Beat Tracking of Systolic Blood Pressure Using Noninvasive Pulse Transit Time During Anesthesia Induction in Hypertensive Patients

Abstract: Beat-to-beat PTT was fairly well correlated with invasive systolic BP and could predict a reduction in systolic BP during anesthesia induction. Beat-to-beat PTT may show potential as a useful noninvasive index of systolic BP when invasive BP is unavailable in high-risk hypertensive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 31 publications
7
47
0
Order By: Relevance
“…Some of the changes such as peak to peak amplitude, rise time, width, slope, PTT and pulse rate recover within 5-10 min of tooth extraction. Our results show the decreased PTT and increased pulse amplitude after the injection of local anesthesia, which are closely agree with the results reported by Kim et al [15]. The pulse wave is influenced by sympathetic activity, vascular stiffness and other factors that influence the local perfusion.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Some of the changes such as peak to peak amplitude, rise time, width, slope, PTT and pulse rate recover within 5-10 min of tooth extraction. Our results show the decreased PTT and increased pulse amplitude after the injection of local anesthesia, which are closely agree with the results reported by Kim et al [15]. The pulse wave is influenced by sympathetic activity, vascular stiffness and other factors that influence the local perfusion.…”
Section: Discussionsupporting
confidence: 93%
“…An acute rise in BP causes vascular tone to increase and hence the arterial wall becomes stiffer which causes PTT to reduce. Kim et al [15] have shown the increased PTT with reduced systolic blood pressure during anesthesia induction in hypertensive patients during kidney transplant surgery and also reported that PTT variability may show potential as a useful noninvasive index of SBP. The PTT has clinically significant association with systolic hypertension at a given time and also enables prediction of changes in BP over a short period [13].…”
Section: Introductionmentioning
confidence: 97%
“…BP changes can be recorded by monitoring changes in PTT. 25 A sudden increase in BP increases the vascular tone, which results in an increase of arterial wall rigidity and shorter PTT. 26 Although there was a higher number of PTT drops in WUS, the difference was not statistically significant.…”
Section: Figure 2-desaturationmentioning
confidence: 99%
“…36 More recently, oximeter-based PTT has been used to obtain accurate measurements of changes in blood pressure that occur during induction of general anesthesia as well as to achieve rapid detection of the onset of hypotension in patients undergoing spinal anesthesia for Cesarean delivery. 37,38 While more validation studies are needed, the near instantaneous response time shown in both of these studies is encouraging. 33,34 In aggregate, these data suggest that PTT, at least over short time periods, provides useful information for immediate detection of hemodynamic changes that might be missed if only an oscillometric cuff method is used for periodic blood pressure assessments.…”
Section: Physiology Of the Ppgmentioning
confidence: 84%